Periurbanização na Metrópole: bairro Chácaras Bom Retiro, Goiânia-GO - Araújo, Leonardo de Castro (2014)
This paper discusses the process of periurbanization in the northern city of Goiânia. For both, the analysis takes as empirical reality the territorial dynamics Chácaras Bom Retiro neighborhood. The process of periurbanization is seen as an action of the metropolis itself, therefore the theoretical analysis incorporates the concepts of metropolization and periurbanization in a complementary way. The origin of the Chácaras Bom Retiro neighborhood is marked by a migratory process of people from the city of Portalegre (RN) with strong rural tradition. Currently, there is significant territorial transformations presente in the neighborhood, a result of the influence and territorial extent of Goiânia metropolis. The natural landscape and the slow time of the place contrast with the metropolitan space. However, the landscape which refers to the field requires a new reading, since urbanity is dispersed by the metropolis also for the rural. This new reality emerges many problems and challenges for the local population, as the difficulty of access to commerce and services, the incomplete implementation of urban infrastructure, the provision of poor public transport service, etc. It is intended to also contribute to the discussion about the question of the Metropolitan Region of Goiânia and reflections on the concepts of periurbanization and metropolization.